Pengaruh Kepemimpinan, Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Klinik Ibnu Sina Kota Balikpapan - Mutiarani Devara; Misna Ariani; Tutik Yuliani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to determine the influence of Leadership, Motivation, and Work Environment on Employees at the Ibnu Sina Clinic in Balikpapan City. The research used quantitative research. The sampling technique used purposive sampling, with a sample size of 38 non-medic employees. Data collection was conducted by distributing questionnaires. This study used Smart-PLS to process the data. The results of this study indicate that Leadership and Motivation variables have no effect on employee performance at the Ibnu Sina Clinic in Balikpapan City. Motivation and Work Environment variables have a positive effect on employee performance at the Ibnu Sina Clinic in Balikpapan City, and the Work Environment variable has a positive effect on employee performance at the Ibnu Sina Clinic in Balikpapan City.